Typology and Feature Checking of Wh-Questions - Ma, Daoshan (PAROLE: Journal of Linguistics and Education, 2017)
From  the  perspective  of  the  syntactic  behavior  of  wh-questions,  natural languages can be classified into four types: Null Spec Language, Single Filled Spec  Language,  Multiply  Filled  Spec  Language  and  Non-Multiply  Filled Spec Language. Data were collected according to the relevance to the present research  from  each  representative  of  the  four  types  of  languages,  namely, Chinese, English, Bulgarian and Czech. Some of the data in the thesis were taken from the previous literature. Others were from self-introspection. The collected data were analyzed from the point of typology and feature checking. Feature checking in wh-questions of these four types of languages seem to be operated quite differently. Pied-piping of the formal features of the wh-words or  wh-phrases  occur  in  English,  Bulgarian  and  Czech  but  not  in  Chinese. However, feature movement in wh-questions of these four types of languages is universal. This finding proves Chomsky’s biological linguistic belief that language is mainly an optimal solution to conditions it must satisfy.